Hospital formularies: need for continuous intervention. Issue 6716 (6th January 1990) - Feely, J; Chan, R; Cocoman, L; Mulpeter, K; O'Connor, P
Abstract : The effects of introducing a hospital formulary alone and with active intervention were compared prospectively with regard to drug costs and the quality of prescribing. Intervention comprised feedback on prescribing habits, peer comparison, and information on drugs. Aspects of prescribing that were not subjected to intervention did not alter. In the year in which intervention occurred generic prescribing rose by 50%; inappropriate prescribing and overall use of third generation cephalosporins fell; and compliance with the recommended list of drugs was good. Overall, drug costs remained static, compared with a projected increase of 0.25 m pounds; in a comparative control hospital drug costs rose by 18%. During the next year, when no form of intervention took place, previous gains were eroded and drug costs rose. Continuous intervention, review, and feedback are required if a formulary is to continue to achieve its objectives.